Ketersediaan Kalium dan Hasil Kedelai (Glycine max L. Merril) pada Tanah Vertisol yang Diberi Mulsa dan Pupuk Kandang - Sudadi Sudadi; Y N Handayati; Sumani Sumani (Caraka Tani: Journal of Sustainable Agriculture, 2007)
The aim of the research was to study the effect of kind of mulches, farmyard manure dosages (FYM), and their interaction on available potassium and yield of soybean on Vertisol. The experiment was conducted at green house on July to December 2002. Soil analysis was done at Soil Science Laboratory, Agriculture Faculty, Sebelas Maret University, Surakarta. It was arranged in Completely Randomized Design (CDR) with two factor and each treatment combination replicated three times. The first factor was kinds of mulch i.e. without mulch, rice straw at 5 ton/ha, and rice hull at 5 ton/ha. The second one was farmyard manure (FYM) dosage, i.e. 0,6 and 12 ton FYM/ha. Data analyzed for F Test and DMRT at 5% significancy and Stepwise Regresion to predict the optimum of soybean yield. The result showed that both kind of mulch and FYM influence available potassium at maximum vegetative phase of soybean, while their interaction significant on available K at harvested  time, seed weight/plant and weight of 100 seeds. Available K increase coinside with FYM dosage. Stepwise Regression Analysis showed that treatment combination for the optimum of available-K at maximum vegetative phase, available-K at harvest time, seed weight/plant, and weight of 100 seeds were rice straw mulch and 2,76 ton FYM/ha, rice straw mulch and 0,035 ton FYM/ha, rice full mulch and 2,57 ton FYM/ha, and rice straw mulch and 1,1017 ton FYM/ha respectively